Corporate social responsibility practices in northern province organisations: managers’ perspective - Thatshayini, P.; Damitha, R.; Pathmashalini, R. (University of Jaffna, 2019)
Business organisations are an integral part of the society. They depend upon the society for their continued existence and growth by impacting it. Therefore, it is believed that they should give back the positive impact of their businesses to the society in return. Hence, Corporate Social Responsibility (CSR), the practice which gives business organisations the opportunity to perform towards the betterment of the society, has become one of the prime business practices in the word today. Though CSR has received such an attention in the global context, the empirical findings suggest that the Sri Lankan organisations are low responsive for CSR. Further, a lack of researches conducted on CSR in Northern Province orgnisations in Sri Lanka could also be noted. Therefore, the aim of this paper is to make an understanding on the current CSR practices i.e. initiation and implementation in Northern Province organisations in Sri Lanka and to identify the lacking areas. The study focused only to explore the perceptions of management on this regard. After a comprehensive literature review, semi-structured interviews were conducted with five respondents, who represented the top management of five selected organisations andwho are well experienced in CSR. The collected data were analysed through manual content analysis. The research findings showed that the CSR practices of Northern Province business organisations are not adequate while a more concern has been given to internal CSR than external CSR activities. Further, nothaving separate division/committee to carryout CSR, designing CSR activities based on head offices’ perspective, lack of community awareness, and lack support from stakeholders and encouraging bodies are the issues that need to be addressed, in order to improve initiation and implementation of CSR in Northern Province organisations in Sri Lanka.
Keywords: Corporate social responsibility (CSR); Initiation; Implementation; Northern province; Sri lanka